If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -1k + -2 = 6k + -11 Reorder the terms: 12 + -2 + -1k = 6k + -11 Combine like terms: 12 + -2 = 10 10 + -1k = 6k + -11 Reorder the terms: 10 + -1k = -11 + 6k Solving 10 + -1k = -11 + 6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6k' to each side of the equation. 10 + -1k + -6k = -11 + 6k + -6k Combine like terms: -1k + -6k = -7k 10 + -7k = -11 + 6k + -6k Combine like terms: 6k + -6k = 0 10 + -7k = -11 + 0 10 + -7k = -11 Add '-10' to each side of the equation. 10 + -10 + -7k = -11 + -10 Combine like terms: 10 + -10 = 0 0 + -7k = -11 + -10 -7k = -11 + -10 Combine like terms: -11 + -10 = -21 -7k = -21 Divide each side by '-7'. k = 3 Simplifying k = 3
| 8x^3-4x^2+7x-1=0 | | 0.4x+3.6=0.3x+1.3 | | (3x-4)+(2x+1)= | | 8(x+2)=7x-7 | | 1.35p=40.5 | | -4+x=6+x | | 3n=14-4 | | 27=x+1+(2x+1)+5x | | 14-(5m+8)=2+3m-12 | | 9x+7y=-9 | | 9x+(-2x)= | | 3n+6=3 | | y=2x^2+9x+7 | | r(x)=10x-.002x^2 | | 27=x+1+2x+1+5x | | 57+x+x+132=165 | | 4x+12(7+x)= | | 6(y+3)+5=47 | | 54n-8=3 | | 3x+20=2x-15 | | 6x+5-2x=2(2x+3) | | 2x^2=x-8 | | f(x)=2x^3-7x^2+13x+40 | | 5(2-5x)-2(3-7x)=10-x+6 | | 5(y+2)+2=32 | | 63=7M+13 | | 3x-15+3x=5+6x-20 | | 2x-7-3x=-5 | | 7+25x=20x+8 | | 2x^2=-8+10x | | 9x+40=-15x-8 | | 8p-27=-7+3 |